Indigenous Sanction of Expulsion in Central Aceh District (Human Rights Perspective) - Valentina Shanty; Adwani Adwani; Azhari Yahya (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2018)
Aceh Province as an Islamic Sharia Regional has culture and customs based on the values of the Quran and Hadith. For the Acehnese people, customs and laws cannot be totally separated that Acehnese customary law continues to grow until the birth of Acehnese Qanun Number 9 of 2008 concerning the Development of Indigenous and Customary Life. In the implementation, the customary sanctions experience some obstacles due to their unwritten characteristic that made them slightly shifted by the presence of national law. As what happens nowadays in Central Aceh District which is famous with its traditional values, there found legal issues for the customary instrument (Sarak Opat) when the customary sanctions considered discriminatory and arbitrary. Therefore, the settlement of customary disputes must be in accordance with humanitarian principles prioritizing the principle of deliberation and peace although many obstacles still exist at the level of implementation because of lack of understanding by both community and customary instruments related to the implementation of customary itself.